Learning in Context: Women in Transition from Situations of Domestic Violence - Margaret L. Cain; Elizabeth Kjar (Adult Education Research Conference, 2001)
This empirical study explores learning among women in a transitional housing program for women and children who have experienced domestic violence. It situates this learning in the context of the women's lives, the program structure, and larger socioeconomic factors.